Climate narratives in educational agendas: On the value of time for pedagogical research and environmental policies - José Antonio Caride; José Gutiérrez Pérez; Pablo Ángel Meira Cartea (Revista Española de Pedagogía)
A matter of time. This could be, in its connotations that are most open to scientific, pedagogical and social interpretation, the principal claim referred to by arguments in which are projected the reflective, methodological, empirical, and documentary concerns of the text we present regarding climate narratives in the educational agendas of the third millennium. In any case, the fact that their approaches raise a wide and varied range of questions about the value of time for pedagogical research and socio-environmental policies cannot be ignored. From this perspective, the aim of this article is to emphasise the importance of educating in time, without further delay, about the challenges posed by the climate emergency, promoting systematic and rigorous research on key issues so that they are addressed in education and society; especially when the slow convergence between climate and education policies can be observed, illustrated here by the Spanish case. We conclude by highlighting that educational research must take into account the rhythms of the crisis: from the temporal dimension (synchronic and diachronic) inherent to anthropogenic climate change, up to the dimension that must be incorporated, as a key factor, in any socio-ecological transition that promotes lifestyles that are ecologically and socially sustainable, fair, and equitable.